PSYCHOLOGICAL LITERACY OF YOUNGER STUDENTS AS A CONDITION OF DEVELOPMENT OF UNIVERSAL EDUCATIONAL AKTIONS - A. M. Prihojan (Вестник Мининского университета, 2017)
The article considers the problem of formation of empathy and decentration as a universal educational actions in primary school on the psychology lessons in elementary school. It is shown that the formation of psychological literacy is a condition for the formation of empathy and decentration as personal competencies of primary school children.